UMKM dan E-Commerce Pada Teknologi - Moch Rifqi Shihabuddin Al Ubaidillah; M Juniar Fajrus Shalah; Muhammad Yasin (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
Micro, Small and Medium Enterprises (MSMEs) play a vital role in the economies of many countries, including Indonesia. Along with the development of information and communication technology, e-commerce has become a crucial platform for MSMEs to expand markets, increase operational efficiency and increase competitiveness. This study examines the impact of e-commerce adoption on MSME performance, with a focus on increasing market access, reducing operational costs, and increasing product and service innovation. The research methodology includes a literature review, secondary data analysis, and case studies of MSMEs that have successfully implemented e-commerce. The research results show that e-commerce provides significant benefits for MSMEs, such as increased sales and efficiency, but also reveals challenges such as the need for increased digital capacity and adequate technological infrastructure. This research concludes that government support and collaboration with the private sector are needed to optimize the potential of e-commerce in empowering MSMEs in the digital era.